Clinicians' experience of providing care: a rapid review - Maha Pervaz Iqbal; Elizabeth Manias; Laurel Mimmo; Stephen Mears; Briony Jack; Liz Hay; Reema Harrison (BMC, 2020)
Abstract Background Health care services internationally are refocussing care delivery towards patient centred, integrated care that utilises effective, efficient and innovative models of care to optimise patient outcomes and system sustainability. Whilst significant efforts have been made to examine and enhance patient experience, to date little has progressed in relation to provider experience. This review aims to explore this knowledge gap by capturing evidence of clinician experience, and how this experience is defined and measured in the context of health system change and innovation. Methods A rapid review of published and grey literature review was conducted utilising a rapid evidence assessment methodology. Seventy-nine studies retrieved from the literature were included in the review. Fourteen articles were identified from the grey literature search and one article obtained via hand searching. In total, 94 articles were included in the review. This study was commissioned by and co-designed with the New South Wales, Ministry of Health. Results Clinician experience of delivering health care is inconsistently defined in the literature, with identified articles lacking clarity regarding distinctions between experience, engagement and work-related outcomes such as job satisfaction. Clinician experience was commonly explored using qualitative research that focused on experiences of discrete health care activities or events in which a change was occurring. Such research enabled exploration of complex experiences. In these contexts, clinician experience was captured in terms of self-reported information that clinicians provided about the health care activity or event, their perceptions of its value, the lived impacts they experienced, and the specific behaviours they displayed in relation to the activity or event. Moreover, clinician's experience has been identified to have a paucity of measurement tools. Conclusion Literature to date has not examined clinician experience in a holistic sense. In order to achieve the goals identified in relation to value-based care, further work is needed to conceptualise clinician experience and understand the nature of measurement tools required to assess this. In health system application, a broader 'clinician pulse' style assessment may be valuable to understand the experience of clinical work on a continuum rather than in the context of episodes of change/care.